2018
DOI: 10.1186/s13071-018-2739-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the interplays between Schistosoma mansoni, praziquantel and the gut microbiome

Abstract: BackgroundSchistosomiasis is a neglected tropical disease burdening millions of people. One drug, praziquantel, is currently used for treatment and control. Clinically relevant drug resistance has not yet been described, but there is considerable heterogeneity in treatment outcomes, ranging from cure to only moderate egg reduction rates. The objectives of this study are to investigate potential worm-induced dysbacteriosis of the gut microbiota and to assess whether a specific microbiome profile could influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 50 publications
6
71
1
1
Order By: Relevance
“…In a previous study in Schistosoma haematobium-infected children, while there was significant alteration of the host's microbiome composition during infection, the administration of praziquantel to uninfected children did not result in microbiome differences compared to baseline measurements (22). Further, in a recent study it has been shown that the presence of certain bacterial genera pretreatment may influence praziquantel efficacy (23). Therefore, the praziquantel/oxamniquine treatment regime used is unlikely to have a direct effect on the gut microbiome.…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study in Schistosoma haematobium-infected children, while there was significant alteration of the host's microbiome composition during infection, the administration of praziquantel to uninfected children did not result in microbiome differences compared to baseline measurements (22). Further, in a recent study it has been shown that the presence of certain bacterial genera pretreatment may influence praziquantel efficacy (23). Therefore, the praziquantel/oxamniquine treatment regime used is unlikely to have a direct effect on the gut microbiome.…”
Section: Discussionmentioning
confidence: 86%
“…Enteric parasite infections are among the most common causes of diarrhea in humans in 198 the developing world. While bacterial infections and the gut microbiome have been well-199 studied, the impact of enteric eukaryotic parasites on the microbiome is not well understood, 200 with some reports showing altered microbiome composition (14,(34)(35)(36)(37) while others showed 201 either modest or no impact (38,39). Because these studies often rely on experimental 202 infection with one or few parasite species, they provide limited insight into the broader impact 203 of enteric parasites on the gut microbiome.…”
Section: Discussion 197mentioning
confidence: 99%
“…However, some studies align with our ndings. For instance, Schneeberger et al suggested that S. mansoni infection (in children) does not affect the gut microbial composition [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using not only animal models but also human clinical samples have demonstrated a clear relationship between gut microbiota alterations and Schistosoma spp. infection [20,21,22,23,24,25]. However, no study has explored the relationship between gut microbiota and S. japonicum infectioninduced liver cirrhosis; the potential role of gut microbiota alterations in disease onset and progression is still unclear.…”
Section: Introductionmentioning
confidence: 99%